Eksplorasi Faktor Harga Layanan untuk Agensi Sosial Media - Alfi Laili Putri; Lina Setiawati; Widi Senalasari (Politeknik Negeri Bandung, 2021)
Eksplorasi Faktor Harga Layanan untuk Agensi Sosial Media